2019
DOI: 10.3389/fphar.2019.00748
|View full text |Cite
|
Sign up to set email alerts
|

From Synthetic Fragments of Endogenous Three-Finger Proteins to Potential Drugs

Abstract: The proteins of the Ly6 family have a three-finger folding as snake venom α-neurotoxins, targeting nicotinic acetylcholine receptors (nAChRs), and some of them, like mammalian secreted Ly6/uPAR protein (SLURP1) and membrane-attached Ly-6/neurotoxin (Lynx1), also interact with distinct nAChR subtypes. We believed that synthetic fragments of these endogenous proteins might open new ways for drug design because nAChRs are well-known targets for developing analgesics and drugs against neurodegenerative diseases. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 57 publications
(79 reference statements)
1
26
0
Order By: Relevance
“…Though the exact target of cardiotoxins are not identified, they are known to induce cytolysis of cardiomyocytes, erythrocytes and also prevent platelet aggregation [10, 35]. Proteins targeting nAChRs will be useful in developing drugs for neurodegenerative diseases and as analgesics [36]. As an example, cobratoxin from Naja kaouthia was tested for neuropathic pain in rats and has shown to have antinociceptive effect [37].…”
Section: Discussionmentioning
confidence: 99%
“…Though the exact target of cardiotoxins are not identified, they are known to induce cytolysis of cardiomyocytes, erythrocytes and also prevent platelet aggregation [10, 35]. Proteins targeting nAChRs will be useful in developing drugs for neurodegenerative diseases and as analgesics [36]. As an example, cobratoxin from Naja kaouthia was tested for neuropathic pain in rats and has shown to have antinociceptive effect [37].…”
Section: Discussionmentioning
confidence: 99%
“…The biological activity of fragments of several other Ly6 proteins, namely, their ability to compete with radioactive α-Bgt for binding to different nAChRs and such their models as AChBPs and ligand-binding domains of individual subunits, as well as the ability of these fragments to inhibit currents in certain nAChR subtypes, was described by us in detail earlier [ 10 ]. The present study confirmed the micromolar affinity of fragments of the central loop II of the Lynx1 protein towards the T. californica nAChR (IC 50 values were in the range 1.1–7.9 μM), showing that the inhibitory activity was higher than that of the full-size protein for the same receptor or AChBPs from L. stagnalis and Aplysia californica [ 25 ] and does not strongly depend on whether the fragment is linear or cyclized ( Figure 1 A).…”
Section: Discussionmentioning
confidence: 99%
“…Linear peptides were prepared by solid-phase peptide synthesis using Fmoc/t-butyl strategy on tritylchloride-polystyrene resin (Intavis, Cologne, Germany) mostly as in [ 10 ]. Polypeptide chain assembly was performed on Syro I automatic peptide synthesizer (MultiSynTech AG, Witten, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparative purification was carried out as described previously 21 using a Gilson HPLC system (333/334 pump with 215 liquid handler) equipped with a YMC Triart 10um 30 × 150 mm column and UV detection at 210 and 280 nm. Peptides elution was achieved by addition of a H 2 O-acetonitrile in the 10-55% gradient with 0.1% v/v CF3COOH.…”
Section: Synthesis Of Hap and Its Analogs Solid-phase Synthesis Utilmentioning
confidence: 99%